Novel Insights into the Etiology, Genetics, and Embryology of Hypoplastic Left Heart Syndrome. Issue 5 (September 2022) - Gabriel, George C.; Yagi, Hisato; Xu, Xinxiu; Lo, Cecilia W.
Hypoplastic left heart syndrome (HLHS) is a relatively rare severe congenital heart defect (CHD) closely linked to other left ventricular outflow tract (LVOT) lesions including bicuspid aortic valve (BAV), one of the most common heart defects. While HLHS, BAV, and other LVOT lesions have a strong genetic underpinning, their genetic etiology remains poorly understood. Findings from a large-scale mouse mutagenesis screen showed HLHS has a multigenic etiology and is genetically heterogenous, explaining difficulties in identifying the genetic causes of HLHS. In Ohia mice, HLHS shows incomplete penetrance. Some mice exhibited small LV with normal aorta, and others a normal LV with hypoplastic aorta, indicating the LV hypoplasia is not hemodynamically driven. In Ohia mutants, HLHS was found to have a digenic modular construction, with mutation in a chromatin modifier causing the small LV phenotype and mutation in Pcdha9 causing the aorta/aortic valve hypoplasia. The Pcdha9 mutation alone can cause BAV, and in the human genome two common deletion copy number variants spanning PCDHA7-10 are associated with BAV. Hence the digenic etiology of HLHS can account for the close association of HLHS, a rare CHD, with BAV, one of the most common CHD. Functional analysis of Ohia HLHS heart tissue showed severe mitochondrial dysfunction in the small LV, while the normal size RV is also affected but milder, suggesting possible role in vulnerability of surgically palliated HLHS patients to heart failure. These findings suggest insights into the genetics of HLHS may yield new therapies for improving outcome for patients with HLHS.